Blau Syndrome Complicated by Atypical Type IIa Takayasu Arteritis - Bikouli, Efstathia Danai C.; Vazeou, Andriani; Xatzipsalti, Maria; Servos, Georgios; Delis, Dimitrios; Maritsi, Despoina N. (Journal of Child Science, 2021)
Blau syndrome (BS) is a rare, autosomal dominant monogenic autoinflammatory disease, usually presenting as a triad of symptoms (granulomatous dermatitis, uveitis, and nonerosive arthritis) and caused by gain-of-function mutations in the nucleotide oligomerization domain 2 (NOD2) gene. However, very few reports in children of copresence of BS with large vessel vasculitis exist. We hereby describe a case of BS associated with clinical features of Takayasu arteritis. An 8.5-year-old boy presented with hypertension, cardiac insufficiency, arthritis, and ocular disease. Among other investigations, he underwent cervical and chest computed tomography and computed tomography angiography scans that revealed the presence of type IIa Takayasu arteritis lesions. Genetic analysis revealed a heterozygous mutation of NOD2 gene leading to the amino acid exchange Arg-587-Cys in the NACHT domain of the NOD2 protein (R587C) as pathogenic cause of BS. He received treatment with prednisolone, methotrexate, and infliximab (antitumor necrosis factor-α) in addition to antihypertensive medication with a favorable clinical response. Cases of BS should be investigated for the coexistence of Takayasu arteritis. However, further research is required to delineate a possible common pathogenic mechanism between the two clinical entities.
Keywords: autoinflammatory disease; Blau syndrome; Takayasu; NOD2; anti-TNF-α